Device-enabled neighborhood-slot allocation for the edge-oriented Internet of Things - Khan, Rahim; Khan, Mushtaq; Shah, Nadir; Al-Rasheed, Amal; Khan, Aftab Ahmad (Frontiers in Computer Science, 2024)
We are very excited to have been allowed to revise our manuscript entitled "Device-enabled Neighborhood-Slot Allocation for the Edge Oriented Internet of Things". We have considered the comments provided by the editor and reviewers. We want to extend our appreciation for taking the time and effort necessary to provide these insightful guidance and suggestions that led us to improve the paper's contents. Specific and short responses to the reviewers' comments are provided below. Moreover, the changes are shown "in Blue" in the revised manuscript.The authors presented and simulated a Device-enabled Neighborhood-Slot Allocation for IoMT. They compare the performance of their proposal with existing algorithms to evaluate their performance. The topics are interesting and aligned with the journal's scope. Nevertheless, some aspects need to be improved before accepting the paper. A series of comments are added to enhance the paper's quality. 1. The last sentence of the first paragraph and the first sentence of the second paragraph of the introduction are too similar. The authors can consider deleting or modifying these sentences.As suggested by the reviewer, first sentence of second paragraph is revised as highlighted in blue for easy follow-up and review.2. In the third paragraph of the introduction, the authors mention wearable devices. Nevertheless, the authors mentioned the application of agriculture and industry in the abstract and introduction. Then, in section 3, the authors focused on IoMT. This is confusing. The authors have to provide a better context for their application field or mention that their proposal can be applied in various scenarios.As suggested by the reviewer, the abstract and introduction sections are revised as highlighted in blue for easy follow-up and review.